A cross sectional and longitudinal study of endodontic and periapical status in an Australian population. (31st May 2017) - Timmerman, A; Calache, H; Parashos, P
Abstract: Background: This study describes the cross sectional and longitudinal data of endodontic and periapical status of new patients presenting to a major dental hospital, and assesses the relationships between tooth‐related variables with apical periodontitis. Methods: The records of 695 patients were randomly selected and the orthopantomograms of these patients up to 31 October 2014 were reviewed by two endodontists. The periapical status of teeth was recorded using the periapical index. The presence and quality of root fillings and coronal restorations were recorded. Statistical analysis included Fleiss' kappa, Cohen's kappa and logistic regression set at P < 0.05. Results: Of 695 patient records and 16 936 teeth examined, 138 (19.9%) patients or 284 (1.7%) teeth had root fillings and 179 (25.8%) patients or 325 (1.9%) teeth had apical periodontitis. Root fillings and coronal restorations were adequate in 34.6% and 69.4% teeth, respectively. A large proportion (47%) of teeth with apical periodontitis remained unchanged in subsequent orthopantomograms. Conclusions: There was lower prevalence of root filled teeth or apical periodontitis in the present study compared with international studies. The frequency of adequate root fillings must be considered unacceptably low. Teeth with apical periodontitis may remain quiescent in the absence of caries or restorative breakdown.